Effects of moisture content on wind erosion thresholds of biochar. (December 2015) - Silva, F.C.; Borrego, C.; Keizer, J.J.; Amorim, J.H.; Verheijen, F.G.A.
Abstract: Biochar, i.e. pyrolysed biomass, as a soil conditioner is gaining increasing attention in research and industry, with guidelines and certifications being developed for biochar production, storage and handling, as well as for application to soils. Adding water to biochar aims to reduce its susceptibility to become air-borne during and after the application to soils, thereby preventing, amongst others, human health issues from inhalation. The Bagnold model has previously been modified to explain the threshold friction velocity of coal particles at different moisture contents, by adding an adhesive effect. However, it is unknown if this model also works for biochar particles. We measured the threshold friction velocities of a range of biochar particles (woody feedstock) under a range of moisture contents by using a wind tunnel, and tested the performance of the modified Bagnold model. Results showed that the threshold friction velocity can be significantly increased by keeping the gravimetric moisture content at or above 15% to promote adhesive effects between the small particles. For the specific biochar of this study, the modified Bagnold model accurately estimated threshold friction velocities of biochar particles up to moisture contents of 10%. Graphical abstract: Highlights: Wind erosion of biochar was assessed through wind tunnel simulations. Moisture content lower than 10% does not prevent erosion of fine particles. Higher moisture increases adhesion of fine particles and weight of large particles. Minimum 15% moisture is recommended for reducing wind erosion of biochar.